Design of Synchronizer Control for Biogas Engine Fuel System - Munahar Suroto; Purnomo Bagiyo Condro; Setiyo Muji; Miftakhudin Yudha; Andrianto Nur Rahmat (E3S Web of Conferences)
Biogas is a new and renewable energy source that offers numerous advantages. It is renewable, environmentally friendly, capable of reducing dependence on fossil fuels, and economically valuable. Additionally, biogas has a high-octane rating, making it suitable for use in high-compression engines. The use of biogas as engine fuel requires adequate quality control, as not all biogases can be used effectively as fuel. Based on previous research, the quality of biogas fuel can be categorized into several clusters: Cluster one: Biogas contains a high level of methane, making it easy to use for engine operation. Cluster two: Biogas has a moderately low methane content, which makes it difficult to use for engine operation. Cluster three: Biogas has a very low methane content, rendering it unsuitable for engine operation. This study focuses on addressing issues related to the utilization of second-cluster biogas. For this cluster, a synchronizer control system is employed to manage the transition process from gasoline to biogas as fuel. The method involves designing an electronic synchronizer control system that operates in multiple steps. The resulting design regulates the entry of biogas through the following steps: The control system deactivates the gasoline check valve. The system opens the first biogas check valve. The system opens the first and second biogas check valves. The system opens the first, second, and third biogas check valves. The designed engine operates smoothly during the transition from gasoline to biogas. However, the control system design does not yet account for factors such as engine temperature, environmental conditions, or the integration of artificial intelligence. These factors can be considered for inclusion in future developments of the synchronizer control system.